Enhanced detection of chronic wasting disease in muscle tissue harvested from infected white-tailed deer employing combined prion amplification assays. - Caitlyn N Kraft; David W Bissinger; Erin E McNulty; Nathaniel D Denkers; Candace K Mathiason (PLoS ONE)
Zoonotic transmission of bovine spongiform encephalopathy or mad cow disease, by presumed consumption of infected beef, has increased awareness of the public health risk associated with prion diseases. Chronic wasting disease (CWD) affects moose, elk, and deer, all of which are frequently consumed by humans. Clear evidence of CWD transmission to humans has not been demonstrated, yet, establishing whether CWD prions are present in muscle tissue preferentially consumed by humans is of increasing interest. Conventional assays including immunohistochemistry (IHC) and enzyme-linked immunosorbent assay (ELISA) lack the sensitivity to detect low concentrations of prions presumed to be present outside neural or lymphatic tissues. Here we combined two prion amplification assays, the product of protein misfolding cyclic amplification (PMCA) applied directly into real-time quaking induced conversion (RT-QuIC) [denoted now as PQ] to demonstrate the presence of prion seeding activity (i.e. prions) in ~55% of hamstring muscles harvested from CWD-positive white-tailed deer. This compares to prion detection in only 10% of the same samples employing standard RT-QuIC. To determine the extent of CWD dissemination within muscle tissues commonly consumed we tested 7 additional muscles from a subset of deer by PQ. Tongue demonstrated the highest level of prions with ~92% positive. All negative controls remained negative in all PMCA and RT-QuIC assays. We conclude that the combination of PMCA with RT-QuIC readout permits detection of low prion concentrations present in muscle tissue of CWD-infected deer. These findings further demonstrate the utility of amplification assays as tools to detect very low levels of prion burden and supports their use to fill knowledge gaps in our understanding of CWD pathogenesis and zoonotic potential.